c = 5
so 3 x c = 15
15-6 = 9
Chat with our AI personalities
When adding positive 9 and negative 6, we can think of it as combining two numbers with opposite signs. To find the sum, we subtract the absolute value of the smaller number from the absolute value of the larger number. In this case, the absolute value of 9 is 9, and the absolute value of 6 is 6. So, 9 - 6 equals 3. Therefore, positive 9 plus negative 6 equals positive 3.
The absolute of any number is a positive number. So that the absolute value of -6-3=9 because -6-3=-9 absolute value of -9=9
15
9-3=6
-6